Chapter New Generation of High Efficient OLED Using Thermally Activated Delayed Fluorescent Materials - Pereira, Luiz (InTechOpen, 2018)
The search for efficient materials for organic light emitting diodes is one of the most imperative research area. The focus is to obtain a bright large area emitter, limited by the low internal quantum efficiency of conventional organic emitters. Recently, a new generation of the organic materials (TADF) with a theoretical internal quantum efficiency up to 100%, opened new frameworks. However, significant challenges persist to achieve full understanding of the TADF mechanism and to improve the OLEDs stability. Starting from the photo-physical analysis, we show the relationship with the molecular electrical carrier dynamics and internal quantum efficiencies. The OLED structure, fabrication, and characterization are also discussed. Several examples for the full color emitters are given. Special emphasis on experimental results is made, showing the major milestones already achieved in this field.